SOC: clay ratio: A mechanistically-sound, universal soil health indicator across ecological zones and land use categories? - Walter W. Wenzel; Alireza Golestanifard; Olivier Duboc (Geoderma)
The European Union has recently launched a proposal for a soil monitoring and resilience directive (“soil monitoring law”, SML), defining the SOC: clay ratio as descriptor of the soil organic carbon (SOC) status, with a ratio of 1/13 separating “healthy” from “unhealthy” soils. Using data of the Lower Austrian soil database, this article explores the mechanistic foundation and applicability of the SOC: clay ratio in the ecologically diverse study region. We observe considerable variation of the SOC: clay ratio among agroecological regions because clay content and SOC are driven by different ecological variables, with clay content related to the texture of parent materials. After stratification by land use (cropland versus grassland), we built multiple regression models starting with an initial set of predictor variables including mean annual precipitation (MAP) and temperature (MAT), clay content, CaCO3 equivalent, amorphous oxyhydroxides of Al (Alo) and Fe (Feo), and pH to identify the main drivers of SOC and their relative importance. The final models explain between 23 and 77  % of the overall SOC variation, and reveal that SOC is primarily controlled by Alo and the CaCO3 equivalent across the entire study region and within most agroecological and soil units, with smaller contributions of clay content and MAP. The set of relevant SOC drivers and their relative importance vary with spatial scale (entire study region versus agroecological and soil units), the aridity index (defined as MAT: MAP) and the state of soil development, as reflected by soil pH. With some notable exceptions, Alo is most important in more humid regions and acidic soils, whereas the relevance of CaCO3 equivalent and clay content increases with pH and aridity.The limited importance of clay content indicates that the SOC: clay ratio is a poor descriptor of soil health in the study region. Moreover, we could not confirm a meaningful functional relation between the SOC: clay ratio and the quality of soil structure derived from visual assessment. These findings challenge the universal use of the SOC: clay ratio as descriptor of soil health, and its threshold of 1/13 to distinguish the soil health status across different ecological zones. If SOC is not primarily driven by clay content, also the use of correction factors to the SOC: clay threshold as suggested by the SML is not appropriate.To derive meaningful regional benchmarks of SOC, we suggest to employ multiple regression analysis with the main SOC drivers as input variables. The regression equation can be used to predict the SOC levels expected for the average management regime of the region at any given values of the relevant main soil and climate drivers. This approach can be further refined by scaling down to the soil unit level, and by developing relations for different, clearly defined categories of soil management, and their calibration to soil functional properties (e.g., air capacity, structure quality scores) in order to link the benchmarks to soil management, soil health and related ecosystem services.